Emergence and evolution of rare ST592 blaNDM-1-positive carbapenem-resistant hypervirulent Klebsiella pneumoniae in China - Huan Zhang; Su Dong; Caiping Mao; Yuejuan Fang; Junjie Ying (Frontiers in Cellular and Infection Microbiology)
ObjectivesThis study aimed to characterize the genomes of two rare ST592 Klebsiella pneumoniae isolates and to explore their evolution into carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKp).MethodsThe minimum inhibitory concentrations (MICs) were determined using a VITEK 2 compact system. Conjugation experiments were conducted using film matings. Whole-genome sequencing (WGS) was performed using the Illumina and Nanopore platforms. The antimicrobial resistance determinants were identified using the ABRicate program in the ResFinder database. Insertion sequences were identified using ISFinder and the bacterial virulence factors identified using the Virulence Factor Database (VFDB). The K and O loci were examined using Kleborate. Multilocus sequence typing (MLST) and replicon type identification were performed by the Center for Genomic Epidemiology. Conjugation-related elements were predicted using oriTfinder. The plasmid structure was visualized using Circos, and a possible evolutionary model was constructed using BioRender.ResultsIsolates KPZM6 and KPZM16 were identified as ST592 and KL57, respectively, and were collected from the same department. The antimicrobial susceptibility testing data revealed that KPZM16 possesses an extensively drug-resistant (XDR) profile, whereas KPZM6 is a susceptible K. pneumoniae. The hybrid assembly showed that both KPZM6 and KPZM16 have one pLVPK-like virulence plasmid carrying the rmpA, rmpA2, and iucABCD-iutA gene clusters. However, strain KPZM16 harbors one IncN plasmid carrying the carbapenem resistance genes blaNDM-1, dfrA14, and qnrS1. The results of the conjugation experiments demonstrated that the plasmid could be transferred to the recipient strain. It is possible that the NDM-1-producing plasmid was transferred from KPZM6 to KPZM16 via conjugation, leading to the formation of CR-hvKp.ConclusionsThis is the first study in which complete genomic characterization of the rare NDM-1-producing ST592 K. pneumoniae clinical isolate was performed. This study provides a possible evolutionary hypothesis for the formation of CR-hvKp via conjugation. Early detection is recommended to avoid the extensive spread of this clone.